O IPTU no município de Santa Maria/RS: um panorama sob a ótica da inadimplência - Gering, Silvia Maria Parmeggiani (2018)
The municipalities should promote the collection of taxes of their competence to carry out their multiple activities for the common good of citizens. In the Municipality of Santa Maria (RS), the Tax on Predial and Urban Territorial Property - IPTU stands out for the low level of collection, influenced, in part, by the default. This comes from several causes and presents several consequences, which can only be softened with its ample knowledge. Therefore, the purpose of this study was to identify the determinants of IPTU default in the Municipality of Santa Maria (RS), seeking to list alternatives for its reduction. So, a descriptive research was used, with a quantitative approach and descriptive and multivariate statistical techniques. The register data and financial data of 126,190 properties registered in the real estate cadaster were sampled. Based on the descriptive statistics, the characteristics and location of the real estate were verified, showing that the sales and taxable values are below the market value, due to the application of reducers and lags of the generic plant of values. Through the observation of the payment options, a default of around 40.00% was verified, and in those, the payment installments delays were of 53.00%. The cross reference tables provided a diagnosis of default, showing that the highest indexes are in residential neighborhoods, whose average nominal income is lower than the average of the municipality; located far from the central area; predominating in registries located in tax zones, whose price of the m² of the land is lower. Through test t was verified that the average of the areas and values are lower for the group of defaulters compared to the regular ones. The logistic regression showed that the default rate is influenced by the tax rate, the existence of irregular area, the increase in the taxable value of the property, favorably manifesting in the individuals, relating to the values and location of the properties, as well as the positions of the taxpayers. Thus, the study pointed to causes to be attributed to the taxpayers, to the institution and to the economic situation. As institutional causes are including the structural and registration deficiencies that hamper collection actions. Hence, it is indispensable to restructure the collection sectors, with adjustments in equipment, computer systems and human resources. Subsequently, in order to reduce delinquency, a broad registry update and intensification of collection should be promoted, through the monitoring of payments, prioritizing the neighborhoods with the largest number of properties, with differentiated action plans for taxpayers who fail to remove a few plots, of those who are habitual debtors. For the first, soft actions; for the others, strict control of reparcelling, immediate sending of the debits for registration in the organs of credit protection and fiscal execution. It was shown that the study about the defaults brought contributions to the institution, to the academy and to the society. As suggestions for future studies it is recommended to research with defaulting taxpayers to identify their profile, income and perceptions.